Engineered red blood cells for capturing circulating tumor cells with high performance. Issue 13 (15th March 2018) - Zhu, Dao-Ming; Wu, Lei; Suo, Meng; Gao, Song; Xie, Wei; Zan, Ming-Hui; Liu, Ao; Chen, Bei; Wu, Wen-Tao; Ji, Li-Wei; Chen, Li-ben; Huang, Hui-Ming; et al.
Abstract : Filtration of circulating tumor cells (CTCs) in peripheral blood is of proven importance for early cancer diagnosis, treatment monitoring, metastasis diagnosis, and prognostic evaluation. Abstract : Filtration of circulating tumor cells (CTCs) in peripheral blood is of proven importance for early cancer diagnosis, treatment monitoring, metastasis diagnosis, and prognostic evaluation. However, currently available strategies for enriching CTCs, such as magnetic activated cell sorting (MACS), face serious problems with purity due to nonspecific interactions between beads and leukocytes in the process of capturing. In the present study, the tumor-targeting molecule folic acid (FA) and magnetic nanoparticles (MNPs) were coated on the surface of red blood cells (RBCs) by hydrophobic interaction and chemical conjugation, respectively. The resulting engineered RBCs rapidly adhered to CTCs and the obtained CTC–RBC conjugates were isolated in a magnetic field. After treatment with RBC lysis buffer and centrifugation, CTCs were released and captured. The duration of the entire process was less than three hours. Cell counting showed that the capture efficiency was above 90% and the purity of the obtained CTCs was higher than 75%. The performance of the proposed method exceeded that of MACS® beads (80% for capture efficiency and 20% for purity) under the same conditions. The obtained CTCs could be successfully re-cultured and proliferated in vitro . Our engineered RBCs have provided a novel method for enriching rare cells in the physiological environment.